Case Report: S100-negative primary anorectal melanoma with elevated Ki67: a case for biology-driven radical resection despite early radiological staging - Ren, Xiangxiang; Xie, Tianhao; Liu, Litao; Jin, Xiaoshi; Ma, Wei; Sun, Jing; Zhang, Meng (Frontiers in Oncology, 2025)
BackgroundPrimary anorectal melanoma (PARM) is a rare and highly aggressive malignancy. Diagnosis is often challenging due to non-specific symptoms and potential S100 negativity on immunohistochemistry (IHC), while optimal surgical management remains debated.Case presentationA 67-year-old woman presented with hematochezia, tenesmus, and overflow pseudodiarrhea. Clinical examination and MRI identified a 2.0 cm ulcerated rectal mass, staged as cT2N0. Initial biopsy revealed atypical melanocytic proliferation. Definitive IHC of the resection specimen confirmed melanoma, showing S100 negativity but positivity for HMB45, Melan-A, and SOX10. A notably high Ki67 proliferation index was observed, escalating from 30% in the biopsy to 60% in the resected tumor. Despite the early radiological stage (cT2N0), the high Ki67 index indicated aggressive tumor biology, prompting a multidisciplinary team to recommend abdominoperineal resection (APR). Adjuvant chemotherapy with temozolomide and cisplatin was administered postoperatively. The patient remained disease-free at 24-month follow-up.ConclusionThis case highlights that S100 negativity does not preclude a melanoma diagnosis when supported by other specific melanocytic markers. Furthermore, a markedly elevated Ki67 index may identify biologically aggressive PARM tumors that could benefit from radical resection, even in the context of early radiological staging. Biology-driven surgical decision-making, complemented by adjuvant therapy, may improve outcomes in this high-risk subset of patients, though larger prospective studies are needed for validation.